Designing an English Coursebook for Senior Executive Administrative Assistants for English Department Students Based on Indonesian National Work Competency Standards (SKKNI) - Mochamad Imron Azami; Noni Mia Rahmawati (J-SHMIC : Journal of English for Academic, 2023)
Designing a comprehensive course book for English for Business is a challenging endeavor that requires a deep understanding of the unique linguistic and professional needs of learners. In the rapidly evolving landscape of international business communication, educators and instructional designers face a lot of obstacles that must be addressed in order to create a truly effective and relevant course book. This study aims to create a coursebook for an English for Business class based on SKKNI in the scheme of executive administrative assistants. The instructor must construct their own coursebook because SKKNI does not give references. Most studies, however, claimed that generating ESP content is challenging due to a lack of sources, assistance, and a national curriculum. Theoretically, this research is based on Borg and Gall's RnD steps, and just 5 steps have been chosen to conduct this research. The researchers conducted expert validation to evaluate the coursebook and administered a questionnaire to students. The coursebook was judged good (73%) by expert validators with some revisions and 79% by students with several features needing improvement in various categories such as typeface, illustration, and mistyped words.